2022
DOI: 10.3389/fsurg.2022.823770
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neuroendoscopic and Microscopic Surgery for Unilateral Hemilaminectomy: Experience of a Single Institution

Abstract: ObjectiveThis study was designed to compare the safety and efficacy of unilateral hemilaminectomy conducted under complete neuroendoscopic visualization (UHNV) relative to unilateral hemilaminectomy under total microscopic visualization (UHMV) for the treatment of patients diagnosed with intraspinal tumors.MethodsIn total, 41 patients undergoing intraspinal tumor resection at Northern Jiangsu People's Hospital were included in this study, including 20 and 21 patients in the UHNV and UHMV groups, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…The current study reported a patient series with IDEM spinal tumors treated via pure endoscopic MISS with a parallel non-expandable tubular retractor, in which the patients achieved good outcomes. All patients improved significantly in the postoperative period and had no serious postoperative complications, which is comparable with the results of previous studies ( 14 , 17 , 25 , 26 ). Therefore, pure endoscopic MISS with a parallel non-expandable tubular retractor may be an effective and safe surgical strategy for IDEM spinal tumor resection.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The current study reported a patient series with IDEM spinal tumors treated via pure endoscopic MISS with a parallel non-expandable tubular retractor, in which the patients achieved good outcomes. All patients improved significantly in the postoperative period and had no serious postoperative complications, which is comparable with the results of previous studies ( 14 , 17 , 25 , 26 ). Therefore, pure endoscopic MISS with a parallel non-expandable tubular retractor may be an effective and safe surgical strategy for IDEM spinal tumor resection.…”
Section: Discussionsupporting
confidence: 90%
“…Caballero-García et al ( 25 ) described the use of an endoscope and a Caspar system in MISS for IDEM spinal tumors. Similarly, Zeng et al ( 26 ) reported endoscopic MISS surgery for the removal of IDEM spinal lesions with a Williams retractor. Dhandapani and Karthigeyan ( 17 ) mainly used the X-tube and Quadrant retractor in pure endoscopic MISS to remove IDEM spinal lesions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Traditional laminectomies, which have been widely used in spinal surgery, are believed to provide adequate exposure to the spinal cord, nerve roots, and tumors, and thus may minimize intraoperative damage to the spinal cord ( 4 ). However, this procedure may result in persistent pain and spinal deformity after surgery due to the destruction of the posterior bony structures, supraspinal ligaments, interspinous ligaments, and paraspinal muscles bilaterally ( 5 ). Tarantino et al ( 6 ) recently reported that about 59.6% of patients experienced severe back or wound pain within a year after using the bilateral approach.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to traditional open decompression surgery, minimally invasive microscopic unilateral laminectomy with bilateral decompression (ULBD) techniques can preserve more intact spinal structures, prevent postoperative instability, and minimize soft tissue injury (7)(8)(9), and it has favorable results in the treatment of LCS (10,11).…”
Section: Introductionmentioning
confidence: 99%